High efficiency high gain low side lobe level and slant polarization monopulse antenna using cavity backed slot coupled patch antenna - Seyed Mohammad Hamidi; Seyed Mohammad Javad Razavi; Seyed Hossein Mohseni Armaki (Scientific Reports)
Abstract In this paper, a multilayer monopulse antenna at Ku-Band with high efficiency, high power handling capability, high gain, 45° linear polarization and low sidelobe is presented. A new slot antenna is proposed as a radiating element based on a cavity-backed slot-coupled patch antenna. Using an enclosed cavity structure reduces coupling between antenna elements, thus increasing the antenna efficiency. The sub-array antenna has been designed to reduce the feed network complexity. A cavity power divider and feeding slots are inserted between the layers of the sub-array to compact it. An innovative feeding network has been designed with two-dimensional Chebyshev distribution. The simulated impedance bandwidth is 11%. The peak gain is 38.4 dBi and the sidelobe level of lower than 18 dB with a half-power beamwidth of approximately 2.4° for sum patterns at the center frequency and efficiency is more than 86% across the bandwidth. The maximum value of null depth for the difference patterns is − 38 dB. The radiation patterns have good symmetry in both E- and H-planes. The simulation results are compared with the results obtained from the built part of the antenna. the measurements results are in good agreement with the simulation.